Nicotiflorin attenuates cell apoptosis in renal ischemia‐reperfusion injury through activating transcription factor 3. Issue 4 (25th February 2021) - Wang, Lin; Li, Chenyu; Guan, Chen; Zhang, Yue; Yang, Chengyu; Zhao, Long; Luan, Hong; Zhou, Bin; Che, Lin; Wang, Yanfei; Zhang, Wei; Zhang, Hui; et al.
Abstract: Introduction: Nicotiflorin is the main characteristic component of Nymphaea candida, which is a natural product that reportedly ameliorates acute injury of the liver and cerebral cortex, but the effect of nicotiflorin on acute kidney injury (AKI) remains unknown. This study aimed to investigate the effects of nicotiflorin on ischaemia/reperfusion (I/R) AKI and the associated mechanisms. Methods: We performed both (a) in vivo experiments with C57BL/6 mice with bilateral renal pedicles clamped for 45 minutes and (b) in vitro experiments with human kidney epithelial cells (HK‐2) exposed to hypoxia/reoxygenation to mimic I/R injury to study the role of nicotiflorin in AKI. Results: In vivo, nicotiflorin administration exerted protective effects on renal injury, as demonstrated by reductions in the levels of caspase3 and Bad ( P < .05), the upregulation of Bcl‐2 expression ( P < .05) and improved renal histologic changes, which suggested that nicotiflorin can alleviate I/R injury and cell apoptosis. In vitro, nicotiflorin at a concentration of 75 μg/mL protected cells from hypoxia, which further confirmed that nicotiflorin exerts beneficial effects on hypoxia/reoxygenation. Through computational molecular docking, we found that activating transcription factor 3 (ATF3) exhibits a robust interaction with nicotiflorin with a simulated binding energy of −9.2°. We verified the interaction of nicotiflorin with ATF3 in HK‐2 cells, and found that nicotiflorin reduced the apoptosis of HK‐2 through ATF3. Conclusion: Based on the above‐described results, nicotiflorin appears to have a beneficial impact on deteriorated renal function, as demonstrated using an experimental I/R model. The underlying mechanisms of nicotiflorin might inhibit HK‐2 cell apoptosis through ATF3. SUMMARY AT A GLANCE: The study suggests that nicotiflorin, the component from a Chinese herb, has protective effect in a mouse model of renal ischaemia/reperfusion injury. By using computational molecular docking analysis and RNA silencing, the authors identified that nicotiflorin ameliorates renal cell apoptosis via activation of transcription factor 3 (ATF3).